2005
DOI: 10.1007/s00000-005-5110-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and development of the secretory cavities of Myrtus communis leaves

Abstract: The structure and development of Myrtus communis L. secretory cavities has been studied in young and expanded leaves, using light and scanning electron microscope. Secretory cavities are continuously formed during leaf development, but in mature leaves the rhythm of their appearance shows steep decrease. Each secretory cavity is developed from a single epidermal cell, which undergoes a periclinal division followed by anticlinal and several oblique cell divisions. The lumen of the secretory cavity is initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 7 publications
3
19
0
7
Order By: Relevance
“…Contradictory views have been suggested concerning the origin of the intercellular space of the secretory cavity. It has been supported that in the vegetative parts of M. communis the lumen is schizogenously formed (Brocheriou and Belin-Depoux, 1974;Kalachanis and Psaras, 2005). Moreover, recent ontogenetic investigations on the vegetative organs of other genera of Myrtaceae (Eucalyptus, Callistemon, Eugenia, Leptospermum, Melaleuca, Psidium) showed schizogenous development of the lumina in this family (Brocheriou, 1976;Brocheriou and Belin-Depoux, 1974;Carr and Carr, 1970;Fahn, 1979).…”
Section: Secretory Structuresmentioning
confidence: 91%
See 4 more Smart Citations
“…Contradictory views have been suggested concerning the origin of the intercellular space of the secretory cavity. It has been supported that in the vegetative parts of M. communis the lumen is schizogenously formed (Brocheriou and Belin-Depoux, 1974;Kalachanis and Psaras, 2005). Moreover, recent ontogenetic investigations on the vegetative organs of other genera of Myrtaceae (Eucalyptus, Callistemon, Eugenia, Leptospermum, Melaleuca, Psidium) showed schizogenous development of the lumina in this family (Brocheriou, 1976;Brocheriou and Belin-Depoux, 1974;Carr and Carr, 1970;Fahn, 1979).…”
Section: Secretory Structuresmentioning
confidence: 91%
“…List et al (1995) reported that glands of M. alternifolia leaves are covered by modified epidermal cells and that under a differential pressure the secreted oil was able to pass the epidermal lining. Kalachanis and Psaras (2005) showed that secretory pockets of M. communis leaves are capped by one to four modified epidermal cells without any opening and that under vacuum of the SEM column the secreted material passed through the cap cells covering the secretory cavity. In accordance with List et al (1995), and Kalachanis and Psaras (2005), our light microscope examinations revealed that the cap cells of the floral secretory cavities of myrtle are thicker-walled epidermal cells, that stain intensely with TBO and PAS.…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations